2021
DOI: 10.1155/2021/6638858
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1L Adjuvant Auxiliary Preparations with 2L Solely Polyethylene Glycol plus Ascorbic Acid Regime for Bowel Cleaning: A Meta‐analysis of Randomized, Controlled Trials

Abstract: The effectiveness of additional usage of adjuvants for bowel preparation is still unclear. This study compared 1L polyethylene glycol plus ascorbic acid with adjuvant drug regimens (1L PEG-AA, lower volume) with 2L polyethylene glycol plus ascorbic acid (2L PEG-A, low volume) to evaluate whether the adjuvants can be used to reduce the standard dosage of purgative further. The PubMed/MEDLINE, EMBASE, Cochrane Library, and Web of Science database were searched for randomized controlled trials (RCTs). The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[24][25][26] Xin Y et al reported that there were no significant differences in appropriate bowel preparation rates and complication rates in a meta-analysis of randomized, controlled trials with 1L PEG and 2L PEG. [27] Instead of improving compliance and taste, 1L PEG has raised concerns regarding the risk of hypernatremia and dehydration in patients with renal dysfunction and electrolyte shifts that can lead to serious clinical consequences. [28] However, several studies have not yet reported serious abnormalities in electrolyte balance.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Xin Y et al reported that there were no significant differences in appropriate bowel preparation rates and complication rates in a meta-analysis of randomized, controlled trials with 1L PEG and 2L PEG. [27] Instead of improving compliance and taste, 1L PEG has raised concerns regarding the risk of hypernatremia and dehydration in patients with renal dysfunction and electrolyte shifts that can lead to serious clinical consequences. [28] However, several studies have not yet reported serious abnormalities in electrolyte balance.…”
Section: Discussionmentioning
confidence: 99%